Associations between cohort derived dementia and COVID-19 serological diagnosis among older Black adults in rural South Africa - Harriman, Nigel Walsh; Bassil, Darina T.; Farrell, Meagan T.; Du Toit, Jacques; Gómez-Olivé Casas, F. Xavier; Tollman, Stephen M.; Berkman, Lisa F. (Frontiers in Public Health, 2024)
Objectives: This study investigates the association between cohort derived dementia and serologically confirmed SARS-CoV-2 infection, an underexplored phenomena in low- and middle-income countries. Examining this relationship in a rural South African community setting offers insights applicable to broader healthcare contexts. Methods: Data were collected from Black South Africans in the Mpumalanga province who participated in the Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa. Cohort derived dementia was developed using a predictive model for consensus-based dementia diagnosis. Multinomial logistic regression models estimated the association between predicted dementia probability in 2018 and SARS-CoV-2 infection risk in 2021, controlling for demographics, socioeconomic status, and comorbidities. Results: Fifty-two percent of the tested participants had serologically confirmed SARS-CoV-2 infections. In the fully adjusted model, cohort derived dementia was significantly associated with over twice the risk of serological diagnosis of COVID-19 (RRR=2.12, p=0.045). Conclusions: Complying with COVID-19 prevention recommendations may be difficult for individuals with impaired cognitive functioning due to their symptoms. Results can inform community-based public health initiatives to reduce COVID-19 transmission among South Africa’s rapidly aging population.